Phylogenetic analysis of HCV‐4d in Turkey: the curious case of Kayseri Province. Issue 3 (16th October 2013) - Ciccozzi, Massimo; Zehender, Gianguglielmo; Polat, Ceylan; Lai, Alessia; Kayman, Tuba; Sorrentino, Chiara; Ebranati, Erika; Cella, Eleonora; Lo Presti, Alessandra; Abacioglu, Hakan
Abstract In Turkey, genotype 1, especially type 1b virus, causes approximately 90% of these infections, while types 2, 3, and 4 exist, albeit in low prevalences and are due to relatively recent and limited introductions. Two recent reports from Kayseri, a relatively large city in Central Anatolia, indicated unusually high prevalence for type 4 infections in the province reaching a 35% among patients admitted to hospitals for treatment of chronic hepatitis C. In this study, the origin, the demographic history, and the dynamic of the epidemic of unusual HCV genotype 4d in Turkey by using Bayesian coalescent‐based method were investigated. A gene flow migration approach was also used to describe the synchronous geographical dispersal and genetic diversification of this unusual genotype in Kayseri province. The Turkish clade had a tMRCA of 44 years corresponding to the year 1967 and seems to have a different origin being completely segregated from the European one. Gene flow migration analysis indicated that Kayseri province appeared to be the epicenter of HCV‐4d epidemic, exporting the infections. The demographic history of HCV‐4d showed that the epidemic started in 1970s year then following a slow exponential growth until 1980s. The Turkish monophyletic clade suggests a segregate circulation of the epidemic in this region mostly due to unsafe parenteral medical procedures (with drug addiction playing a relatively negligible role). J. Med. Virol. 86:454–460, 2014. © 2013 Wiley Periodicals, Inc.